THE ROLE OF EDUCATION IN THE ECONOMIC DEVELOPMENT OF UZBEKISTAN (International journal of artificial intelligence, 2025)
This article discusses the pivotal role of education in the socio-economic development of Uzbekistan. Since gaining independence, Uzbekistan has undergone significant reforms in various spheres, including higher education. The state prioritizes the creation of a new Renaissance by fostering talented scientists and specialists through quality education. The paper highlights the government's strategic efforts to enhance the education system, its adaptation to modern economic demands, and the link between educational quality and sustainable economic growth. Investments in human capital and the expansion of educational autonomy are identified as key factors for national competitiveness and economic security. The ongoing educational reforms aim to align training programs with market needs and improve youth employment opportunities, ensuring Uzbekistan’s prosperity in the global arena.